Roman Pottery and Glass Manufactures Proceedings of the 4th International Archaeological Colloquium (Crikvenica, 8-9 November 2017). - Lipovac Vrkljan, Goranka (Archaeopress Roman Archaeology Ser., 2022)
32 papers consider issues of pottery production in the wider Adriatic area during Roman times, in particular relation to landscape and communication features, ceramic building materials, as well as general studies on ceramic production, pottery and glass finds.